Answer:
This is me drawing notes in the blank
Doodle* doodle* drawing noise* drawing noise* There you go ;)
The answer is 25, leave a like (:
The results of the composite functions are:
<h3>What are composite functions?</h3>
Composite functions are functions that are obtained by combining two or more functions together
Assume that:
Then the computation of the composite functions are as follows:
<h3>Function (f * g)(x)</h3>
![(f \times g)(x) = f(x) \times g(x)](https://tex.z-dn.net/?f=%28f%20%5Ctimes%20g%29%28x%29%20%3D%20f%28x%29%20%5Ctimes%20g%28x%29)
![(f \times g)(x) = (2x-3) \times (3x)](https://tex.z-dn.net/?f=%28f%20%5Ctimes%20g%29%28x%29%20%3D%20%282x-3%29%20%5Ctimes%20%283x%29)
![(f \times g)(x) = 6x^2-9x](https://tex.z-dn.net/?f=%28f%20%5Ctimes%20g%29%28x%29%20%3D%206x%5E2-9x)
<h3>Function f(g(x))</h3>
We have: ![f(x) = 2x - 3](https://tex.z-dn.net/?f=f%28x%29%20%3D%202x%20-%203)
This gives
![f(g(x)) = 2g(x) - 3](https://tex.z-dn.net/?f=f%28g%28x%29%29%20%3D%202g%28x%29%20-%203)
So, we have:
![f(g(x)) = 2(3x) - 3](https://tex.z-dn.net/?f=f%28g%28x%29%29%20%3D%202%283x%29%20-%203)
![f(g(x)) = 6x - 3](https://tex.z-dn.net/?f=f%28g%28x%29%29%20%3D%206x%20-%203)
<h3>Function g(f(x))</h3>
We have: ![g(x) = 3x](https://tex.z-dn.net/?f=g%28x%29%20%3D%203x)
This gives
![g(f(x)) = 3f(x)](https://tex.z-dn.net/?f=g%28f%28x%29%29%20%3D%203f%28x%29)
So, we have:
![g(f(x)) = 3(2x - 3)](https://tex.z-dn.net/?f=g%28f%28x%29%29%20%3D%203%282x%20-%203%29)
![g(f(x)) = 6x - 9](https://tex.z-dn.net/?f=g%28f%28x%29%29%20%3D%206x%20-%209)
Read more about composite functions at:
brainly.com/question/10687170
Answer:
then subtitute x to find <FGH